The Role of NLRP3 and IL-1β in Refractory Epilepsy Brain Injury - Wu, Chunfeng; Zhang, Gang; Chen, Lei; Kim, Samuel; Yu, Jie; Hu, Guo; Chen, Jing; Huang, Yanjun; Zheng, Guo; Huang, Songming (Frontiers in Neurology, 2020)
Objective: To investigate the roles and mechanisms of inflammatory mediators NLRP3 and IL-1β in refractory epilepsy brain injury. Method: First, the brain tissue and peripheral blood of children undergoing intractable temporal lobe epilepsy surgery were selected as research objects. The expression of NLRP3 in brain tissue and IL-1β in blood was measured. The model of temporal lobe epilepsy was established using wild-type and NLRP3 knockout 129 mice. Pilocarpine was injected intraperitoneally in the experimental group and isovolumetric saline was injected intraperitoneally in the control group (n=8 in each group). The expressions of IL-1β in the peripheral blood, cerebral cortex, and hippocampus of mice were measured by ELISA at 3h, 24h, 3d and 7d after modeling. FJB and TUNEL methods were used to determine necrosis and apoptosis of hippocampal neurons, respectively, and the expression of NLRP3 in the cortex was measured by immunofluorescence methods. Result: (1) The level of IL-1β in the peripheral blood of children with intractable temporal lobe epilepsy was higher than that of the control group (t=2.813, P=0.01). There was also a positive correlation with the onset time of a single convulsion (r=0.9735, P < 0.05). The expression of NLRP3 in the cerebral cortex of patients with refractory temporal lobe epilepsy was higher compared to that of the control group. (2) The expression of NLRP3 in the hippocampus of wild-type mice increased 3 days after modeling and decreased slightly at 7 days, but still remained higher than control group expression. The level of IL-1β in peripheral blood was significantly higher than control group levels at 3 days (t=8.259, P<0.0001). The level of IL-1β in peripheral blood of NLRP3 knockout mice was lower than that in the wild type group at 3 days (t=3.481，P=0.004). At day 7, the neuronal necrosis and apoptosis in the CA3 region of the hippocampus decreased. Conclusion: NLRP3 may be involved in the development of refractory epilepsy. Inhibiting NLRP3 may alleviate local brain injury by down-regulating IL-1β. The levels of IL-1β in peripheral blood of patients with intractable epilepsy may reflect the severity of convulsion.